The five games of Mr Edgar Allan Poe: A study of strategic thought in 'The Purloined Letter'. (November 2020) - Read, Daniel
This paper investigates strategic thinking in the fictional world of Edgar Allan Poe's 'The Purloined Letter'. This short story has been rightly celebrated for its explicit analysis of strategic reasoning in which players attempt to outwit one another, which involves accounting for how they are all attempting to outwit one another. I differ from previous analyses by examining how the actors can often be wrong in their explicit analysis and consider the strategic actions they take rather than those they claim to take. Using elementary game theory, I describe the five games (and suggest a sixth) that make up the strategic heart of the story. These include games of signalling, screening, negotiation, revenge and a unique game called the 'pincer'. I consider how literary sources like 'The Purloined Letter' can provide insights into the applicability of strategic analysis in the 'real world'.